Revitalisasi Pendidikan Islam di Sekolah dalam Menghadapi Krisis Moral Peserta Didik - Mardiati M; Nursia Nursia; Zulbina Zulbina; Rosiana Syahbaniar; Amaluddin Amaluddin (FKIP UNSULTRA, 2026)
Islamic education plays a strategic role in shaping students' character amid the increasing moral crisis in the digital era. The rapid development of information technology has improved access to learning while simultaneously contributing to various moral challenges, including cyberbullying, declining communication ethics, misuse of social media, and reduced academic integrity. These conditions highlight the urgency of revitalizing Islamic education to remain relevant in responding to contemporary challenges. This study aims to analyze the challenges faced by Islamic education in addressing students' moral crises, identify factors influencing the effectiveness of character development, and formulate revitalization strategies based on the synthesis of previous studies. This research employed a literature review method using a qualitative descriptive approach. Relevant literature published between 2020 and 2025 was collected from Scopus, Google Scholar, ERIC, Dimensions, Crossref, and Garuda databases. The collected studies were analyzed using thematic analysis through identification, selection, synthesis, and interpretation of research findings. The results indicate that the revitalization of Islamic education should emphasize curriculum reform, technology-based learning innovation, teacher competency development, the establishment of a religious school culture, and strong collaboration among schools, families, and communities. Furthermore, integrating Islamic values with digital literacy effectively strengthens students' religious character, responsibility, honesty, and digital ethics. Therefore, revitalizing Islamic education represents a comprehensive strategy for developing students who are morally upright, spiritually grounded, and capable of using digital technology critically, ethically, and responsibly in accordance with Islamic values.